Transcriptional regulation of virulence factors Hla and phenol-soluble modulins α by AraC-type regulator Rbf in Staphylococcus aureus - Bo Fang; Banghui Liu; Baolin Sun (Elsevier, 2020)
Staphylococcus aureus is a gram-positive pathogenic bacterium and is capable of secreting numerous toxins interfering directly with the host to cause acute infections. Rbf, a transcriptional regulator of AraC/XylS family, has been reported to promote biofilm formation in polysaccharide intercellular adhesion (PIA) mediated manner to cause chronic infections. In this study, we revealed the new virulence-mediated role of Rbf that can negatively regulate the hemolytic activity. Furthermore, Rbf can specifically bind to the hla and psmα promoters to repress their expression, resulting in significantly decreased production of phenol-soluble modulins α (PSMα) and alpha-toxin. Accordingly, the rbf mutant strain exhibited the increased pathogenicity compared to the wild-type (WT) strain in a mouse subcutaneous abscess model, representing a type of acute infection by S. aureus. Collectively, our results provide a novel insight into the virulence regulation and acute infections mediated by Rbf in S. aureus.